(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
The 3D reconstruction of the houses in the Central District of the city of Nora was created by the use of Revit Architecture software and has been designed to show the changes which occurred in the area during the II-III century AD phase and in Late Antiquity. The 3D models of individual houses, which are based on the documentation of the excavation, were included in a project of reconstruction of the entire block, in order to recreate the volumetric look and make immediately clear the various aspects of this complex urban context.